(untitled) (Global Journal of Science Frontier Research, 2018)
The aim of the research was to find an alternative way of getting sperm of Clarias gariepinus apart from a living fish which will reduce the cost of live catfish male broodstocks for induce breeding. Dead males broodstocks were bought from Wukari fish market at 5.30pm and were transported to Biological Sciences Fish hatchery in a Polyethene bag and were kept over night in 100litre bowl with water at a level of 80litre. The bowl was not covered in case of jump out. The dead fish sperms were removed carefully and stored in sterilized small bowls containing 0.9% Nomal saline at 7.0am the following day which were later used to fertilize the stripped eggs after a latency period of 8.00hrs (15.30hrs) from hypophysation. The fertilized eggs were spread on the kakabans in a single layer to prevent clumping of eggs in the incubator and flow-through water system was opened for availability of oxygen for the developing embryos. The result revealed that hatching started on the second day after hypophysation at 11.00am. Feeding started two days after hatching with 0.2-0.3mm blue crown feed bought from Jos. The fry survived beyond the experimental period of two weeks from hatching.